1999
DOI: 10.1111/j.1572-0241.1999.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Esophageal Squamous Cell Carcinoma: Analysis of Clinicopathological and Biological Factors

Abstract: En bloc esophagectomy may provide a rather satisfactory survival rate for patients with early stage ESCC. However, for patients with distant lymph node metastasis and those with more than three lymph nodes involved, radical surgical resection, even combined with postoperative chemoradiotherapy, cannot improve survival. The prognostic value of biological markers, including PCNA, EGFR, HER-2/neu, and p53, however, is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 45 publications
4
43
0
2
Order By: Relevance
“…This has been well established in previous studies conducted with nearly the same immunohistochemical procedures, together with a lack of correlation to prognosis, which is consistent with our findings (Sarbia et al, 1994;Hardwick et al, 1997;Shimada et al, 1999;Wang et al, 1999;Ahn et al, 2002;Rosa et al, 2003). P53 mutations are Diffuse EGFR staining and reduced overall survival L Gibault et al peculiarly frequent in high-SCCO incidence areas like Brittany (Audrezet et al, 1993), where we performed our study; some geographic specificity might also be implicated.…”
Section: P53 Protein In Sccosupporting
confidence: 92%
“…This has been well established in previous studies conducted with nearly the same immunohistochemical procedures, together with a lack of correlation to prognosis, which is consistent with our findings (Sarbia et al, 1994;Hardwick et al, 1997;Shimada et al, 1999;Wang et al, 1999;Ahn et al, 2002;Rosa et al, 2003). P53 mutations are Diffuse EGFR staining and reduced overall survival L Gibault et al peculiarly frequent in high-SCCO incidence areas like Brittany (Audrezet et al, 1993), where we performed our study; some geographic specificity might also be implicated.…”
Section: P53 Protein In Sccosupporting
confidence: 92%
“…Therefore, our result was presumably influenced by the factors of cell differentiation, tumour invasion, and lymph node metastasis. Some reports have demonstrated that the degree of cell differentiation is a useful prognostic factor in ESCC patients (Torres et al, 1999;Wang et al, 1999). Invasion and metastasis, the main causes of death in most cancer patients, remain the most important but least understood aspects of cancer.…”
Section: Fak-overexpression (−) Fak-overexpression (+)mentioning
confidence: 99%
“…Expression of nm23-H1 in the pathologic sections was detected by an immunoperoxidase method as previously described (Wang et al, 1999a(Wang et al, , 2002. Paraffin blocks were sectioned at the thickness of 4 mm.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%